Peningkatan Kemampuan Komunikasi pada Pendamping Lapangan Penyakit Menular Seksual di Kota Makassar - Fairus P. Idris; Andi Asrina; Yusriani (Window of Community Dedication Journal, 2022)
One of the groups contributing to sexually transmitted infections (STIs) is homosexuals (gays,waria, and male sex men/GWL) who behave in an unsafe manner and hide their risky status fromtheir sexual partners. GWL is said to be risky if they don't come out about their sexualorientation and many GWLs are not caught or not joined by the community, so their presence isdifficult to detect. This service program aims to improve partners' Health Communication skillsand use of media in promoting Health related to changing GWL behavior through training andpractice. This activity is in the form of training with the participants being field outreachworkers from the Gaya Celebes Foundation, Makassar City. After the training, there was anincrease in the understanding and skills of field facilitators in communicating behavior changeto at-risk groups.